A status assessment of selected data synthesis products for ocean biogeochemistry - Nico Lange; Toste Tanhua; Benjamin Pfeil; Hermann W. Bange; Siv K. Lauvset; Marilaure Grégoire; Dorothee C. E. Bakker; Steve D. Jones; Björn Fiedler; Kevin M. O’Brien; Arne Körtzinger (Frontiers in Marine Science, 2023)
Ocean data synthesis products for specific biogeochemical essential ocean variables have the potential to facilitate today’s biogeochemical ocean data usage and comply with the Findable Accessible Interoperable and Reusable (FAIR) data principles. The products constitute key outputs from the Global Ocean Observation System, laying the observational foundation for information and services regarding climate and environmental status of the ocean. Using the Framework of Ocean Observing (FOO) readiness level concept, we present an evaluation framework for biogeochemical data synthesis products, which enables a systematic assessment of each product’s maturity. A new criteria catalog provides the foundation for assigning scores to the nine FOO readiness levels. As an example, we apply the assessment to four existing biogeochemical essential ocean variables data products. In descending readiness level order these are: The Surface Ocean CO 2 Atlas (SOCAT); the Global Ocean Data Analysis Project (GLODAP); the MarinE MethanE and NiTrous Oxide (MEMENTO) data product and the Global Ocean Oxygen Database and ATlas (GO 2 DAT). Recognizing that the importance of adequate and comprehensive data from the essential ocean variables will grow, we recommend using this assessment framework to guide the biogeochemical data synthesis activities in their development. Moreover, we envision an overarching cross-platform FAIR biogeochemical data management system that sustainably supports the products individually and creates an integrated biogeochemical essential ocean variables data synthesis product; in short a system that provides truly comparable and FAIR data of the entire biogeochemical essential ocean variables spectrum.

A Global Ocean Oxygen Database and Atlas for Assessing and Predicting Deoxygenation and Ocean Health in the Open and Coastal Ocean - Marilaure Grégoire; Véronique Garçon; Hernan Garcia; Denise Breitburg; Kirsten Isensee; Andreas Oschlies; Maciej Telszewski; Alexander Barth; Henry C. Bittig; Jacob Carstensen; Thierry Carval; Fei Chai; et al. (Frontiers in Marine Science, 2021)
In this paper, we outline the need for a coordinated international effort toward the building of an open-access Global Ocean Oxygen Database and ATlas (GO 2 DAT) complying with the FAIR principles (Findable, Accessible, Interoperable, and Reusable). GO 2 DAT will combine data from the coastal and open ocean, as measured by the chemical Winkler titration method or by sensors (e.g., optodes, electrodes) from Eulerian and Lagrangian platforms (e.g., ships, moorings, profiling floats, gliders, ships of opportunities, marine mammals, cabled observatories). GO 2 DAT will further adopt a community-agreed, fully documented metadata format and a consistent quality control (QC) procedure and quality flagging (QF) system. GO 2 DAT will serve to support the development of advanced data analysis and biogeochemical models for improving our mapping, understanding and forecasting capabilities for ocean O 2 changes and deoxygenation trends. It will offer the opportunity to develop quality-controlled data synthesis products with unprecedented spatial (vertical and horizontal) and temporal (sub-seasonal to multi-decadal) resolution. These products will support model assessment, improvement and evaluation as well as the development of climate and ocean health indicators. They will further support the decision-making processes associated with the emerging blue economy, the conservation of marine resources and their associated ecosystem services and the development of management tools required by a diverse community of users (e.g., environmental agencies, aquaculture, and fishing sectors). A better knowledge base of the spatial and temporal variations of marine O 2 will improve our understanding of the ocean O 2 budget, and allow better quantification of the Earth’s carbon and heat budgets. With the ever-increasing need to protect and sustainably manage ocean services, GO 2 DAT will allow scientists to fully harness the increasing volumes of O 2 data already delivered by the expanding global ocean observing system and enable smooth incorporation of much higher quantities of data from autonomous platforms in the open ocean and coastal areas into comprehensive data products in the years to come. This paper aims at engaging the community (e.g., scientists, data managers, policy makers, service users) toward the development of GO 2 DAT within the framework of the UN Global Ocean Oxygen Decade (GOOD) program recently endorsed by IOC-UNESCO. A roadmap toward GO 2 DAT is proposed highlighting the efforts needed (e.g., in terms of human resources).

Toward a Comprehensive and Integrated Strategy of the European Marine Research Infrastructures for Ocean Observations - Juan Jose Dañobeitia; Sylvie Pouliquen; Truls Johannessen; Alberto Basset; Mathilde Cannat; Benjamin Gerrit Pfeil; Maria Incoronata Fredella; Paola Materia; Claire Gourcuff; Giuseppe Magnifico; Eric Delory; Joaquin del Rio Fernandez; et al. (Frontiers in Marine Science, 2020)

Constraining the Oceanic Uptake and Fluxes of Greenhouse Gases by Building an Ocean Network of Certified Stations: The Ocean Component of the Integrated Carbon Observation System, ICOS-Oceans - Tobias Steinhoff; Thanos Gkritzalis; Siv K. Lauvset; Steve Jones; Ute Schuster; Are Olsen; Meike Becker; Roberto Bozzano; Fabio Brunetti; Carolina Cantoni; Vanessa Cardin; Denis Diverrès; et al. (Frontiers in Marine Science, 2019)

Ocean FAIR Data Services - Toste Tanhua; Sylvie Pouliquen; Jessica Hausman; Kevin O’Brien; Pip Bricher; Taco de Bruin; Justin J. H. Buck; Eugene F. Burger; Thierry Carval; Kenneth S. Casey; Steve Diggs; Alessandra Giorgetti; et al. (Frontiers in Marine Science, 2019)

Data Management Strategy to Improve Global Use of Ocean Acidification Data and Information - Hernan Carcia; Cathy Cosca; Alex Kozyr; Emilio Mayorga; Cynthia Chandler; Robert Thomas; Kevin O'Brien; Ward Appeltans; Steve Hankin; Jan Newton; Angelica Gutierrez; Jean-Pierre Gattuso; et al. (Oceanography, 2015)